2022
DOI: 10.3390/medicina59010094
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome Occurring after mRNA COVID-19 Vaccination in a Patient with Graves’ Disease

Abstract: Cardiovascular events such as myocarditis following mRNA COVID-19 vaccination are increasing. We present a 67-year-old postmenopausal woman with Takotsubo Syndrome and Graves’ disease after mRNA COVID-19 vaccination. She developed chest pain and shortness of breath one week after vaccination. An electrocardiogram revealed ST elevation in the precordial leads. Coronary angiography revealed the absence of obstructive coronary artery disease, and the left ventriculography showed a typical feature with apical ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Of the 19 patients from the included studies, 13 [2][3][4][5][6][7][8][9]11,12,14,16,17 of them adhere to the established diagnostic criteria of TTS according to the diagnostic algorithm of TTS published by the European Heart Journal in 2018, 27 but the remaining may need further cardiac tests to confirm the diagnosis. Three patients presented with typical clinical symptoms of TTS and had typical apical ballooning of the left ventricle by echocardiography or ventriculography, but lacking CMR to exclude acute myocarditis given the presence of corresponding red flags such as fever 15,19 or elevated c-reactive protein. 13 Another patient presented with hypokinesia of the inferior wall after vaccination and subsequently developed a left ventricular aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 19 patients from the included studies, 13 [2][3][4][5][6][7][8][9]11,12,14,16,17 of them adhere to the established diagnostic criteria of TTS according to the diagnostic algorithm of TTS published by the European Heart Journal in 2018, 27 but the remaining may need further cardiac tests to confirm the diagnosis. Three patients presented with typical clinical symptoms of TTS and had typical apical ballooning of the left ventricle by echocardiography or ventriculography, but lacking CMR to exclude acute myocarditis given the presence of corresponding red flags such as fever 15,19 or elevated c-reactive protein. 13 Another patient presented with hypokinesia of the inferior wall after vaccination and subsequently developed a left ventricular aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported takotsubo syndrome (TTS) development in the setting of vaccination. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] TTS triggered by vaccines is extremely rare, and published literature available so far is limited to case reports. There is no large-scale systematic review examining the association between vaccines and TTS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing surveillance and reporting of vaccine-related adverse events, including TCM, are crucial for refining risk-benefit assessments and optimizing vaccination strategies. Establishing standardized diagnostic criteria and management guidelines for vaccine-induced TCM is imperative to ensure timely and effective interventions [ 14 ]. Future research should focus on elucidating the specific mechanisms linking COVID-19 vaccination, especially mRNA vaccines, to the development of TCM.…”
Section: Reviewmentioning
confidence: 99%
“…TCM: takotsubo cardiomyopathy, LVEF: left ventricular ejection fraction, M: male, NR: not reported, F: female, ECG: electrocardiography, mRNA: messenger ribonucleic acid Source:[8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25] …”
mentioning
confidence: 99%